Protected Area of Integral Protection of the Atlantic Forest Biome: Management Council as an instrument for verification of potentialities and problems - Silva, Gabriela Albuquerque Lucio da; Riondet-Costa, Daniela Rocha Teixeira; Botezelli, Luciana (Ciência e Natura, 2022)
In a capitalist society, dictated by irrational consumption and use of natural resources without measuring consequences, environmental policies have become necessary to reconcile the relationship between society and the environment. The Brazilian National System of Conservation Units (SNUC – Sistema Nacional de Unidades de Conservação) is one of these policies. This study seeks to analyze a specific type of Conservation Unit (UC – Unidade de Conservação), which is classified as a National Park, the Itatiaia National Park (PNI – Parque Nacional do Itatiaia). The objective was to highlight the park’s socio-environmental problems and potentialities through the Management Council. To do so, data were collected through reviewing the council’s meeting minutes; the identification of potentialities and problems; and use of the SWOT matrix. Thus, problems such as land tenure, budget issues and wildfires were verified. As for potentialities, it was noted that the Council has a well-developed structure and park’s facilities are excellent. More problems were found than potentialities. Still, one can consider that one of the keys to solving the difficulties encountered would be participatory management through Freirean communication, as well as changes in Brazilian public policy.